Caminhares e ciclos: um estudo da consciência corporal na arte e em suas poéticas à luz da perspectiva epistemológica da neurociência - Oliveira, Paulo Ricardo Gonçalves de (2020)
This master's thesis presents as a theme a study of body awareness in art in an epistemological perspective of neuroscience, which in an explanatory research methodology authenticates itself with the causes of a fact experienced in a state of health in Portugal, as well as a presentation of the proposed objectives encompassing qualitative / explanatory research. The descriptive case study is highlighted, which according to Yin (2001), strengthens the research strategy by covering both specific collection approaches in data analysis in this specific case. Dialogues between knowledge are reflected in the reflections of the causal relations of the aspect of the body and its movement in the performing arts, philosophy of mind and neuroscience. Having as theoretical scope the theories of Damasio (2000), to discuss the relations of the conscience in diverse areas of the knowledge as; Thomas Nagel (1974) and Amstrong (1981), also discusses the philosophy of mind and the concepts of performance and performativity presented by Schechner (2010). In this study, theoretical relations with the performing arts were sought for a journey of new paths to neuroscientific practices that focus on body awareness. From the elements raised in the investigation, it can be inferred that art is in communion with all areas of knowledge and therefore has a sustainable logical discourse in neurosciences, because it is a significant part of human life.